Strengthening Spatial Ability of Madrasah Ibtidaiyah Students through Learning Assisted by “PUTAR” Two-Dimensional Shape Puzzle Media - Bagus Hidayatulloh; Mohammad Nurwahid (International Journal of Public Devotion, 2026)
Spatial ability is one of the essential aspects in mathematics learning, particularly in understanding geometric concepts. This study aims to enhance the spatial ability of MI Nurul Huda students through the use of “PUTAR” media (Two-Dimensional Shape Puzzle). The method employed in this study is community service–based research conducted through a series of activities, including teacher training, implementation of the learning media, and evaluation of students’ learning outcomes. The results indicate that the use of “PUTAR” media significantly improves students’ spatial ability, learning participation, and teachers’ competence in integrating innovative instructional media.Penguatan Kemampuan Spasial Siswa Madrasah Ibtidaiyah melalui Pembelajaran Berbantuan Media “PUTAR” Puzzle Bangun DatarABSTRAKKemampuan spasial merupakan salah satu aspek penting dalam pembelajaran matematika, khususnya dalam memahami konsep geometri. Penelitian ini bertujuan untuk melatih kemampuan spasial siswa MI Nuru Huda dengan menggunakan media "PUTAR" (Puzzle Bangun Datar). Metode yang digunakan dalam penelitian ini adalah pengabdian masyarakat melalui serangkaian kegiatan, termasuk pelatihan guru, penerapan media pembelajaran, dan evaluasi hasil belajar siswa. Hasil penelitian menunjukkan bahwa penggunaan media "PUTAR" secara signifikan meningkatkan kemampuan spasial siswa, partisipasi belajar, serta kompetensi guru dalam mengintegrasikan media inovatif.Kata Kunci :Kemampuan Spasial; Media "PUTAR"; Puzzle Bangun Datar; Pembelajaran Matematika